Locating the past in its silence: history and marketing theory in India. (18th May 2015) - Varman, Rohit; Sreekumar, Hari
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to argue, while examining the history of marketing theory in India, that the discipline is ahistorical, serves large business interests and is shaped by hegemonic Western knowledge. Design/methodology/approach – The primary sources of data were the marketing doctoral dissertations, working papers, teaching material and research publications produced in the top management schools in India from the 1960s up to the present period. Findings – The historical review reveals that the marketing theory in India is characterized by dependence on the West and elision of the country's rich business history. It further shows that the discipline in India focuses on research problems and issues which are more appropriate to a Western context, and remains detached from local realities. Moreover, the discipline is characterized by a narrow managerial orientation. Research limitations/implications – Findings from the paper will be of value to researchers who wish to understand the Indian marketing thought. Practical implications – Findings from the paper will be of value to academics and policy makers who wish to create more independent and contextually informed and sensitive management programs. Social implications – The paper reveals the extent to which the education and institutions in India are influenced by the West, and aims to motivate academics and policy makers to understand local knowledge and ways of knowing. Originality/value – The main contribution of this paper is to show that the marketing discipline in India has been ahistorical and is shaped by hegemonic Western knowledge.